Sistem Informasi Penjualan Roti di Toko Mitha Bakery Palu Menggunakan Framework Laravel - Putra, Alviano Yossia; Beeh, Yos Richard (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Mitha Bakery is a Bakery that offers various types of bread, including white bread and brown bread, with undoubted quality. Established in early 2020 in Palu, Central Sulawesi, this shop has experienced a significant increase in sales, from 80 loaves per day in 2022 to more than 300 loaves per day in 2023. To improve service quality, Mitha Bakery designed a sales system web-based using the Laravel Framework and MySQL as the data base. This system is designed to make it easier for customers to obtain information about products and place orders without having to come directly to the shop. This research aims to design and implement an effective and efficient sales system, as well as providing practical benefits for stores and academic contributions through real applications of programming knowledge. With this system, obstacles related to distance, time and limited facilities can be overcome, so that customers can make purchases more comfortably and quickly.